Signos identitários na comunidade de Varginha : construção narrativa da alteridade - Prado, Gustavo José Jordan (2012)
This currency study aims to trace a methodological experimentation in the Ethnography and Literature area. To do so, it uses as parameters for this experiment the cinematographic work of Jean Rouch and his proposal of ethnofiction. The intention bases on the construction of literary tales using ethnography as a way of reaching reality through fiction. In this sense, the work was divided into two stages: 1) Ethnographic preparation in which seek to identify ways of significations of identity traits – called up identity-signs – and belonging in the community of Varginha, in Santo Antonio do Leverger-MT using the inscription of social discourse (Geertz, 1973) and metalinguistic (Bakhtin, 1963) as tools to inquire about cultural events in the community; and 2) The proper construction of a faction (Geertz, 2003), one hybrid genre, which unveils the culture studied, as well as to problematize the very ethnographic discourse.